A Novel Inhibitor of 9-cis-Epoxycarotenoid Dioxygenase in Abscisic Acid Biosynthesis in Higher Plants - Han, Sun-Young (American Society of Plant Biologists, 2004)
Abscisic acid (ABA) is a major regulator in the adaptation of plants to environmental stresses, plant growth, and development. In higher plants, the ABA biosynthesis pathway involves the oxidative cleavage of 9-cis-epoxycarotenoids, which may be the key regulatory step in the pathway catalyzed by 9-cis-epoxycarotenoid dioxygenase (NCED). We developed a new inhibitor of ABA biosynthesis targeting NCED and named it abamine (ABA biosynthesis inhibitor with an amine moiety). Abamine is a competitive inhibitor of NCED, with a K(i) of 38.8 μm. In 0.4 m mannitol solution, which mimics the effects of osmotic stress, abamine both inhibited stomatal closure in spinach (Spinacia oleracea) leaves, which was restored by coapplication of ABA, and increased luminescence intensity in transgenic Arabidopsis containing the RD29B promoter-luciferase fusion. The ABA content of plants in 0.4 m mannitol was increased approximately 16-fold as compared with that of controls, whereas 50 to 100 μm abamine inhibited about 50% of this ABA accumulation in both spinach leaves and Arabidopsis. Abamine-treated Arabidopsis was more sensitive to drought stress and showed a significant decrease in drought tolerance than untreated Arabidopsis. These results suggest that abamine is a novel ABA biosynthesis inhibitor that targets the enzyme catalyzing oxidative cleavage of 9-cis-epoxycarotenoids. To test the effect of abamine on plants other than Arabidopsis, it was applied to cress (Lepidium sativum) plants. Abamine enhanced radicle elongation in cress seeds, which could be due to a decrease in the ABA content of abamine-treated plants. Thus, it is possible to think that abamine should enable us to elucidate the functions of ABA in cells or plants and to find new mutants involved in ABA signaling.